Introduction of CAD-CAM technology in dental education: a student and teacher perspectives - Fukuhara-Nakama, Mary (2023)
This paper describes the student and teacher's perceptions of the process of introducing CAD-CAM technology in dental education. A cross-sectional and descriptive study was carried out; two questionnaires validated by expert judgment were used for data collection, and descriptive statistics were applied. It was obtained that 57.9 % of the students and 37.5 % of the teachers considered that the teaching of CAD-CAM technology should begin in the third year of studies; the training was helpful for both students and teachers, and this technology would be a procedure of choice for treatment with fixed prosthesis if they had it available. It is concluded that students and teachers positively perceive the introduction of CAD-CAM technology in the clinical courses of the dental career, and it would be a resource of choice for fixed prosthesis treatment.